2017
DOI: 10.5590/jsbhs.2017.11.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Posttraumatic Stress Symptoms From Chronic Terror Attacks on Southern Israel

Abstract: Since 2000, the southern Israeli town of Sderot and neighboring rural region, Otef Aza, have been frequently exposed to nearly identical terror attacks by Hamas. While only a small minority of Otef Aza residents have been diagnosed with posttraumatic stress disorder (PTSD), more than a third of Sderot residents have been so diagnosed. Factors such as social cohesion and ideology may be the unique factors that protect Otef Aza residents from PTSD; however, a gap in the literature exists as to how these same fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Consistent with previous researchers (Gelkopf et al, 2012;Mor & Dardeck, 2017;Stein et al, 2013) who examined prevalence of PTSD symptoms among Sderot, Israel, residents, 354 (27.4%) of the 1,290 study participants reported they had been diagnosed with PTSD.…”
Section: Descriptive Statisticssupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with previous researchers (Gelkopf et al, 2012;Mor & Dardeck, 2017;Stein et al, 2013) who examined prevalence of PTSD symptoms among Sderot, Israel, residents, 354 (27.4%) of the 1,290 study participants reported they had been diagnosed with PTSD.…”
Section: Descriptive Statisticssupporting
confidence: 85%
“…The target population for this study included residents of southern Israel who have been exposed to terror attacks since 2000 (Gelkopf et al, 2012;Mor & Dardeck, 2017;Stein et al, 2013). Participants were recruited voluntarily in southern Israel.…”
Section: Methods Samplementioning
confidence: 99%
“…This study intends to expand knowledge on attitudes toward capital punishment within societies that experience chronic terrorism by focusing on Israeli society. The chronic state of terrorism in Israel claimed the lives of hundreds (Israel Magen David Adom Ambulance Service, 2016), caused a significant long-term psychological effect on citizens (Mor & Dardeck, 2017) and raised the question of capital punishment for terrorists. Since most of the studies were conducted in the U.S., we based our literature review and hypotheses on these studies.…”
Section: The Current Researchmentioning
confidence: 99%
“…These attacks cause death, injury, substantial property loss, and disruption of daily life. As such, the attacks and the continuous threat of attacks have yielded significant long-term psychological stress, including post-traumatic stress disorder (PTSD) ( Mor & Dardeck, 2017 ; Nuttman-Shwartz & Shoval-Zuckerman, 2016 ).…”
Section: Introductionmentioning
confidence: 99%